Affective Resistance: Objects Of Korean Popular Music - Gitzen, Timothy (Penerbit Universiti Sains Malaysia (USM Press), 2013)
In September 2009, the leader of the South Korean boy band 2PM, Park Jaebeom (a Korean American from Seattle), ceremoniously "left" Korea after the discovery of a controversial posting on his Myspace account from before he debuted as a singer. Fans were outraged about the extent to which Jaebum was "disciplined" for his past comments and wasted no time in displaying this outrage in the form of protests, sit-ins and performances.